Dynamic Compression and Constitutive Model in Fe-27Mn-10Al-1C Duplex Lightweight Steel - Pengfei Cao; Dazhao Li; Shaobin Bai; Yongan Chen; Haitao Lu (Crystals, 2024)
Fe-Mn-Al-C lightweight steels have been of significant interest due to their excellent mechanical properties and unique microstructures. However, there has been limited focus on the dynamic deformation. Here, we systematically investigate the mechanical responses over various strain rates and corresponding microstructure evolution in quasi-static and dynamic compression to reveal the transition of deformation mechanisms. The present lightweight steel exhibits a significant strain rate effect, with the yield strength increasing from 735.8 to 1149.5 MPa when the strain rate increases from 10−3 to 3144 s−1. The deformation in ferrite under high-strain-rate loading is dominated by wave slip, forming a cellular structure (cell block). Meanwhile, the deformation in austenite is dominated by planar slip, forming dislocation substructures such as high-density dislocation walls and microbands. In addition, the deformation twinning (including secondary twinning)- and microband-induced plasticity effects are responsible for the excellent dynamic compression properties. This alloy delays damage location while maintaining high strength, making it ideal for shock loading and high-strain-rate applications. The Johnson–Cook (J–C) constitutive model is used to predict the deformation behavior of lightweight steel under dynamic conditions, and the J–C model agrees well with the experimental results.